Factors related to liability for damages for adverse events occurring in long-term care facilities. - Mayumi Tsuji; Hiroki Fukahori; Daisuke Sugiyama; Ardith Doorenbos; Katsumi Nasu; Yuriko Mashida; Hirofumi Ogawara (PLoS ONE, 2023)
Globally, residents of long-term care facilities (LTCFs) often experience adverse events (AEs) and corresponding lawsuits that result in suffering among the residents, their families, and the facilities. Hence, we conducted a study to clarify the factors related to the facilities' liabilities for damages for the AEs that occur at LTCFs in Japan. We analyzed 1,495 AE reports from LTCFs in one Japanese city. A binomial logistic regression analysis was conducted to identify factors associated with liability for damages. The independent variables were classified as: residents, organizations, and social factors. In total, 14% of AEs resulted in the facility being liable for damages. The predictors of liability for damages were as follows: for the resident factors, the increased need for care had an adjusted odds ratio (AOR) of 2.00 and care levels of 2-3; and AOR of 2.48 and care levels of 4-5. The types of injuries, such as bruises, wounds, and fractures, had AORs of 3.16, 2.62, and 2.50, respectively. Regarding the organization factors, the AE time, such as noon or evening, had an AOR of 1.85. If the AE occurred indoors, the AOR was 2.78, and if it occurred during staff care, the AOR was 2.11. For any follow-ups requiring consultation with a doctor, the AOR was 4.70, and for hospitalization, the AOR was 1.76. Regarding the type of LTCF providing medical care in addition to residential care, the AOR was 4.39. Regarding the social factors, the reports filed before 2017 had an AOR of 0.58. The results of the organization factors suggest that liability tends to arise in situations where the residents and their family expect high quality care. Therefore, it is imperative to strengthen organizational factors in such situations to avoid AEs and the resulting liability for damages.